Basic hope according to Erik H. Erikson and stress coping strategies among pregnant women - Terelak, Jan Felicjan; Demkiewicz, Joanna (Studia Psychologica: Theoria et praxis, 2006)
Conducted empiric research refers to a relationship between stress coping strategies regarding childbirth among women waiting for their first child and basic hope according to E. Erikson. In order to measure a level of hope Basic Hope Inventory constructed by J. Trzebiński and M. Zięba was used. A questioner The Coping  Orientations  to Problems  Experienced constructed by C.S. Carvera, M.F. Scheiera, J.K. Weintrauba was used to measure stress coping strategies connected with first pregnancy. Material included 112 women pregnant for the first time. In the first period of pregnancy were 56 women (10-25 week), and 56 women were preparing for delivery (29-39 week). Results indicate that Theoretic Construct .Basic Hope. can be one of factors, which explain women attitudes regarding motherhood. Strong hope influences behavior and emotions of women causing birth stress reduction and adequate identification with a new role- mother role.